(untitled) (Biological Sciences - PJSIR, 2023)
The deficiency of micronutrients in soil caused by Eucalyptus has been investigated at three sampling sites in Pattoki, Punjab, Pakistan. Eucalyptus absorb more water and nutrients than the other trees usually absorb. One Eucalyptus tree absorbs the water of about 100 trees. Eucalyptus makes the soil nutrient deficit. The major problem is that Eucalyptus are affecting the soil moisture and the nutrients of the soil. The objectives of the study, a point-centered quarter sampling technique was used to collect the soil samples. Which were taken at the depth of 36. The main biological activity lies in these organic horizons (0-30 cm). Soil sample analysis demonstrated that the soil pH of the concerned study area was alkaline. The micronutrient contents (B, Zn, OM and P) were highly deficient in all selected sites. Moreover, significantly higher concentrations of Ca were identified in the study area. The linear regression model was applied to validate the relationship between variables. The study showed that sole cultivation of Eucalyptus tends to lower soil fertility and therefore, detailed investigation of nutrient dynamics and their effects on soil quality is a dire requirement. Cultivation of Eucalyptus only has a propensity to lower soil fertility by depletion of important soil nutrients (B, Zn and P). Based on results, it is recommended to interplant Eucalyptus with other leguminous plants and in addition to good agronomic practices such as the use of nitrogenous and phosphate fertilizers to replenish the nutrient availability and biological activity in the soil associated with Eucalyptus planting.